2015
DOI: 10.1002/bit.25643
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling of novel regio‐selective fatty acid double bond hydratases from Lactobacillus acidophilus involved in the selective oxyfunctionalization of mono‐ and di‐hydroxy fatty acids

Abstract: The aim of this study is the first time demonstration of cis-12 regio-selective linoleate double-bond hydratase. Hydroxylation of fatty acids, abundant feedstock in nature, is an emerging alternative route for many petroleum replaceable products thorough hydroxy fatty acids, carboxylic acids, and lactones. However, chemical route for selective hydroxylation is still quite challenging owing to low selectivity and many environmental concerns. Hydroxylation of fatty acids by hydroxy fatty acid forming enzymes is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…In previous studies, parameters influencing hydratase activity and product yield were identified . Up to five conditions including glucose concentration, cofactor addition (NADH, FAD), reducing agents (DTT, glutathione), salt concentration, enzyme stabilization, and incubation temperature were analyzed simultaneously in four rounds of optimization with biotransformation setups designed by MODDE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, parameters influencing hydratase activity and product yield were identified . Up to five conditions including glucose concentration, cofactor addition (NADH, FAD), reducing agents (DTT, glutathione), salt concentration, enzyme stabilization, and incubation temperature were analyzed simultaneously in four rounds of optimization with biotransformation setups designed by MODDE.…”
Section: Resultsmentioning
confidence: 99%
“…All tested enzymes only gave 10‐hydroxy fatty acids as products, whereas a hydratase from Macrococcus caseolyticus introduced a second water molecule on incubation with linoleic, α‐linoleic, and γ‐linoleic acid . Moreover, two novel regioselective hydratases from Lactobacillus acidophilus were identified, which convert cis ‐12 unsaturated fatty acids to the corresponding ( S )‐13‐hydroxy products and longer polyunsaturated fatty acids (PUFAs; C16–C22), resulting in the formation of 12‐, 13‐, 14‐, and 15‐hydroxy fatty acids, respectively . The best characterized hydratase is the oleate hydratase from E. meningoseptica ( Em ‐OAH, GQ144 652).…”
Section: Introductionmentioning
confidence: 99%
“…However, a strict regioselectivity for water addition to the cis -9 double bond of unsaturated fatty acids was observed for most enzymes, whereas FAHs hydrating the cis -12 double bond are underrepresented. In fact, since the discovery of a bacterial strain forming a 13-hydroxy fatty acid from LA (Hudson et al 1998), only three enzymes catalysing the hydration of a cis -12 double bond were identified (Volkov et al 2010; Joo et al 2012a; Kim et al 2015), and only the LA hydratase LHT-13 from L. acidophilus LMG 11470 added water exclusively to the cis -12 double bond of LA, α-LnA, and γ-LnA (Kim et al 2015). A unique exemption from this apparently strict regioselectivity was discovered by functional characterization of FA-HY1 and FA-HY2 (57% amino acid sequence identity) from L. acidophilus NTV001 after heterologous expression in E. coli (Hirata et al 2015).…”
Section: Enzymes For Hydration and Their Propertiesmentioning
confidence: 99%
“…The hydration reaction of unsaturated fatty acids was discovered in the early 1960s, during a study on the hydration of oleic acid using a Pseudomonas strain [9,10]. Afterwards, a number of other microorganisms proved to be able to perform this transformation [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] but the enzymes responsible for the hydration step (oleate hydratases) have been characterized only recently [26], receiving growing attention both from chemists and biologists [27][28][29][30][31][32][33][34][35][36][37]. It is worth noting that different putative oleate hydratase have been cloned from a number of bacteria strains, but none of them have been used for the industrial synthesis of HFAs.…”
Section: Introductionmentioning
confidence: 99%